Effect of trace Ni addition on microstructure, mechanical and corrosion properties of the extruded Mg–Gd–Y–Zr–Ni alloys for dissoluble fracturing tools - J. Wang; T. Li; H.X. Li; Y.Z. Ma; K.N. Zhao; C.L. Yang; J.S. Zhang (Journal of Magnesium and Alloys, 2021)
Magnesium alloys, a novel functional material for the fabrication of fracturing tools, are being paid more and more attentions recently due to their relatively high mechanical properties and fast dissolubility ability after fracturing. In this study, the novel extruded Mg–10Gd–3Y–0.3Zr–xNi alloys will be reported and their microstructure, mechanical and corrosion behaviors will be also studied. The results show that Ni contents influence phase precipitation behaviors. With adding 0.2 wt% Ni, a large amount of Zr7Ni10 phases will be precipitated insides α-Mg matrix, directly leading to degradation of strength and large corrosion rate. With further increasing Ni contents, the precipitation phases can be changed from Mg5RE to 18R-LPSO structure, resulting in higher mechanical properties and faster corrosion rate. Moreover, adding Ni element also change the texture orientation by influencing the precipitation behavior of the alloys. The alloys invented in this paper have attained the highest compressive and tensile properties among all the reported dissoluble magnesium alloys. This work is beneficial in understanding the role of Ni in the magnesium alloys and provides more materials alternatives for the fabrication of dissoluble fracturing tools.